Effectiveness and safety use of botulinal toxin compared to others medicinal alternatives in patients with focal dystonia - Yoany Mesa Barrera; Tania Elena Hernández Rodríguez; Yanneris Parada Barroso (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: medical treatment for focal dystonia is initially indicated as a treatment prior to application of botulinal toxin (BTx), but due to, generally does not respond satisfactorily to the treatment; it is necessary to reach this final stage with the application of botulinal toxin. Objective: To determine the effectiveness and safety use of botulinal toxin in patients with focal dystonia who have received other treatment lines. Material and Methods: A randomized, double-blind study in a 35 patient's cohort with dystonia, administrating botulinal toxin type A (Botox) to 19 patients and the other 16 continued medical treatment for 4 months which previously were treated with other therapeutic alternatives for more than 3 years without a satisfactory response. Results: There was a predominance in women with a 74.3%; the most common focal dystonia was blepharospasm; the drug more used were benzodiazepines; there was a significant reduction in scale scores after 3 months; the onset of action was 4 days after shot, loss of effect at 11 weeks; patients and researchers clinical impression; regarding the treatment, was of slight to marked improvement; as well as tolerableness evaluation as very good for 85%. Conclusion: The application effectiveness of botulinal toxin in reducing involuntary spasms in patients with dystonia is greater than other medicinal therapeutic alternatives with good safety and tolerability, which confirmed this treatment as a first-line treatment in these entities.   Keywords: Botulinal toxin, focal dystonia, Benzodiazepines, safety, effectiveness, involuntary spasms.